Inquiry-Scaffolding Learning Model: Its Effect on Critical Thinking Skills and Conceptual Understanding - Wartono, Wartono; Alfroni, Yohana Fransiska; Batlolona, John Rafafy; Mahapoonyanont, Natcha (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
This study aimed to examine the effect of inquiry-scaffolding on critical thinking skills and conceptual understanding. The research design used was a mixed-method embedded experimental model. The samples were 64 students. Two-way ANOVA test results for critical thinking skills and conceptual understanding are the same, where the significance value of the learning model = 0.00 (smaller than the alpha value of 0.05). It means that there are differences in critical thinking skills and conceptual understanding of students who learn by inquiry-scaffolding models ( IS) with conventional models. The interaction value between the learning model and the initial ability to critical thinking skills (CTS) is 0.502, while the conceptual understanding is 0.788. It means that there is no interaction between the learning model and the initial ability to CTS, or conceptual understanding. The results of advanced tests with the Tukey test prove that CTS and the conceptual understanding of students with high ability who experience learning with IS are higher than students with high ability in conventional learning. The same thing also applies to students with low initial ability. Thus, it was concluded that the learning model with an inquiry-based scaffolding technique was superior in improving CTS and conceptual understanding, on students with high and low initial abilities. Therefore, this technique can be used in other learning by using different moderator variables